PENANGANAN DUGAAN PEMERASAN DALAM PENERAPAN RESTORATIVE JUSTICE DALAM PERATURAN POLISI NO.08 TAHUN 2021 BAGI PENYALAHGUNAAN NARKOTIKA DI PANTI REHABILITASI - Kusumah, R. Wikra Febrian (jurnal.unprimdn.ac.id, 2024)
Rehabilitation Center is a place. In this study, researchers used the normative juridical method, which is research focused on examining the application of rules or norms in positive law. This method is carried out to know the handling of allegations of extortion in the application of restorative justice against drug abuse in rehabilitation centers and to find out the implementation of restorative justice in Perpol No. 8 of 2021 against drug abuse in rehabilitation centers. This study found that this restorative justice approach involves law enforcement officials, families, and communities, considering addicts and victims as individuals who need rehabilitation. Measures to prevent extortion in rehabilitation centers, respond to reports, investigate, enforce the law, and protect and support victims should be provided. Education and collaboration with relevant agencies are also important. Restorative justice can address drug abuse holistically, protect individual rights, and create a safe rehabilitation environment. Synergy from law enforcement officials, stakeholders, and the community is needed to tackle drug abuse, especially among children, adolescents, and the younger generation. Restorative justice approaches help victims recover, create a safer environment, and minimize community unrest. Its implementation needs to involve various parties to increase the effectiveness of drug case resolution and provide rehabilitation opportunities for drug users.